Graffiti and Architecture - Bagina, Elena (project baikal, 2018)
Graffiti on the walls of houses is a symptom of the society’s disease, which causes indifference towards architecture. Tolerance towards graffiti leads to degradation of urban environment. The attempts to ‘tame’ graffitists are ineffective.